2020
DOI: 10.21873/invivo.11821
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life of Breast Cancer Survivors Attending an Exercise Intervention Study: A Five-year Follow-up

Abstract: Background/Aim: As the number of breast cancer survivors is increasing, their long-term health-related quality of life (HRQoL) has become an important issue. The aim of the study is to follow up the HRQoL of breast cancer survivors (BCS) in a prospective randomized exercise intervention study and to compare HRQoL to that of the agematched general female population. Patients and Methods: Following adjuvant treatment, 537 patients aged 35-68 and capable of exercise training were randomized to a 12-month exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Therefore, it was difficult for the patients to integrate HIT/HIRT into daily life on their own. There is only a limited number of studies that followed breast cancer patients over 1-2 years reporting inflammation, performance and well-being and even less, which monitored such data after HIT/HIRT [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was difficult for the patients to integrate HIT/HIRT into daily life on their own. There is only a limited number of studies that followed breast cancer patients over 1-2 years reporting inflammation, performance and well-being and even less, which monitored such data after HIT/HIRT [13].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, alternatives to moderate aerobic intensity exercise in cancer therapy like high intensity exercises for strength, endurance or in combination are only rarely examined [11,12]. In addition, there are even fewer studies that followed breast cancer patients over years [13], although it was shown that lifestyle modifications could prevent about one-third of all cases of breast cancer [14]. Adherence to different training regimes also need further examination [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…During the intervention (i.e., the first year after adjuvant treatment), the survivors' HRQoL improved in both the intervention and control groups measured with the EORTC QLQ-C30, but no effect of the exercise intervention on HRQoL was detected at one-or five-year follow-ups [13,14]. At five-year followup, the HRQoL of the survivors, measured with the 15D, still remained below the population level [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have examined the ability and effects of dietary and physical activity interventions to change modifiable lifestyle behaviors among breast cancer survivors 3 . These interventions could lead to better cancer and health outcomes, including a reduced risk of breast cancer mortality 4‐6 and improved physical function, fatigue, and quality of life 7‐9 . A meta‐analysis of >12,000 women with breast cancer demonstrated that postdiagnosis physical activity reduced breast cancer mortality by 34% and reduced all‐cause mortality by 41% 10 .…”
Section: Introductionmentioning
confidence: 99%
“…3 These interventions could lead to better cancer and health outcomes, including a reduced risk of breast cancer mortality [4][5][6] and improved physical function, fatigue, and quality of life. [7][8][9] A meta-analysis of >12,000 women with Cancer June 1, 2021 breast cancer demonstrated that postdiagnosis physical activity reduced breast cancer mortality by 34% and reduced all-cause mortality by 41%. 10 Unfortunately, the study populations for many of these interventions consisted mostly of relatively younger non-Hispanic White (NHW) women.…”
Section: Introductionmentioning
confidence: 99%